Synthesis and characterization of eco-friendly carboxymethyl cellulose based carbon foam using electron beam irradiation. (15th October 2018) - Kim, Hong Gun; Kwac, Lee Ku; Kim, Yong-Sun; Shin, Hye Kyoung; Rhee, Kyong-Yop
Abstract: Carbon foams were prepared by carbonization process without additional stabilization process after manufacturing carboxymethyl cellulose (CMC) composites using a facile electron beam irradiation (EBI) method. A gel fractionation technique was used to study cross-linking degree of infusible structure in the produced CMC composite materials. We observed an increase in cross-linking with increasing CA concentration and EBI doses between 20 kGy and 80 kGy. The CMC composite prepared using 4 wt% CA and 80 kGy EBI represents the highest gel fraction value of ∼98%, showing the highest carbon yields and compressive strength due to the increase of cross-linked parts in carbon foam obtained from these CMC composites, which lowers break defects after carbonization. In addition, available surface area was estimated via Brunauer-Emmett-Teller analysis of the carbon foam samples. The carbon foam produced from the CMC composite treated with 4 wt% CA via 80 kGy resulted in highest specific surface area of 372.06 m 2 /g and adsorption pore size of 2.20 nm indicating greater interaction between gas and the carbon atoms.